Teachers’ perceptions on environmental citizenship: A systematic review of the literature - Georgiou, Yiannis; Hadjichambis, Andreas Ch.; Hadjichambi, Demetra (My University, 2021)
As we are living amid an unprecedent environmental crisis, the need for schools to em-power students into environmental citizenship is intensifying. Teachers are considered as the main driving force in fostering students’ environmental citizenship. However, a critical question is how teachers conceive environmental citizenship and whether their perceptions of environmental citizenship are well-informed. There is an urgent need to investigate teachers’ perceptions, considering their crucial role in the formation of students’ environmental citizenship. This study examines teach-ers’ perceptions of environmental citizenship through a systematic review and thematic analysis of relevant empirical studies. The selected studies (n = 16) were published in peer-reviewed journals during the timespan of the last twenty-five (25) years (1995–2020). The thematic findings of this review revealed that teachers’ perceptions: (a) manifest a relatively decreased understanding of environmental citizenship, (b) are narrowed down to the local scale, individual dimension and private sphere, (c) affect teaching practices, (d) are multi-dimensional, defined by inter-related components, (e) vary according to teachers’ educational/cultural background and personal identity, (f) affect other environmental constructs defining teachers’ professional identity, (g) can be enhanced during teacher education, (h) can be also improved during professional development initiatives. These findings bear significant implications for researchers, policymakers, as well as for teacher educators in the field of Environmental Education.
Keywords: Education for Environmental Citizenship (EEC); Environmental citizenship; Environmental Ed-ucation; Teacher education; Teachers’ perceptions